2010
DOI: 10.1103/physrevlett.104.123605
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Interference of Tunably Indistinguishable Photons from Remote Organic Molecules

Abstract: We demonstrate two-photon interference using two remote single molecules as bright solid-state sources of indistinguishable photons. By varying the transition frequency and spectral width of one molecule, we tune and explore the effect of photon distinguishability. We discuss future improvements on the brightness of single-photon beams, their integration by large numbers on chips, and the extension of our experimental scheme to coupling and entanglement of distant molecules.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
181
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(183 citation statements)
references
References 28 publications
1
181
1
Order By: Relevance
“…Our modified Hong-OuMandel scheme measures the coincidence counts when two photons leave at the same side of a 50:50 beamsplitter, and the second order correlation functions for the two-photon interference effect between two emitters with orthogonal ( ) and parallel ( ∥ ) polarized photons are given by [47][48][49] (1)…”
Section: Methodsmentioning
confidence: 99%
“…Our modified Hong-OuMandel scheme measures the coincidence counts when two photons leave at the same side of a 50:50 beamsplitter, and the second order correlation functions for the two-photon interference effect between two emitters with orthogonal ( ) and parallel ( ∥ ) polarized photons are given by [47][48][49] (1)…”
Section: Methodsmentioning
confidence: 99%
“…In the high-temperature limit k B T Λ α we have is governed by an effective PDC Hamiltonian (Dorfman and Mukamel, 2012b). Bath effects can become important for remote emitters and have been introduced phenomenologically (Lettow et al, 2010) below. We present a microscopic description of PCC with bath fluctuations by formulating the signal in the joint field-matter space measured by simultaneous time-and-frequency resolved detection.…”
Section: Spectral Diffusionmentioning
confidence: 99%
“…The resonant case is especially important for potential spectroscopic applications (Mukamel, 1995), where unique information about entangled matter (Lettow et al, 2010) can be revealed. Other examples are molecular aggregates and photosynthetic complexes or biological imaging .…”
Section: Time-and-frequency Resolved Type-i Pdcmentioning
confidence: 99%
See 2 more Smart Citations